1988
DOI: 10.1111/j.1365-2788.1988.tb01400.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term memory difficulties and Down's syndrome

Abstract: Nonretarded (NR) individuals typically show better short-term memory for brief sequences of auditory than visual information (the modality effect). The present study attempted to determine whether the failure of Down's syndrome (DS) individuals to show the modality effect is due to the verbal-expressive demands of oral responding in memory tasks. DS, NR and MR (non-DS mentally retarded) subjects listened to or looked at increasingly long sequences of digits and attempted to recall them either orally or manuall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 16 publications
(15 reference statements)
2
30
0
1
Order By: Relevance
“…Many individuals with DS have articulation difficulties (Cody and Kamphaus 1999) which can affect speech production and intelligibility (Hamilton 1993, Gunn andCrombie 1996). Removing or reducing the verbal response requirement of verbal short-term memory tasks does not improve memory in individuals with DS (Marcell and Weeks 1988, Laws et al 1996, Jarrold et al 2002. Jarrold et al (2000) found no difference in articulation rates of individuals with DS and individuals with moderate learning difficulties, despite significantly poorer digit span performance in the individuals with DS.…”
mentioning
confidence: 99%
“…Many individuals with DS have articulation difficulties (Cody and Kamphaus 1999) which can affect speech production and intelligibility (Hamilton 1993, Gunn andCrombie 1996). Removing or reducing the verbal response requirement of verbal short-term memory tasks does not improve memory in individuals with DS (Marcell and Weeks 1988, Laws et al 1996, Jarrold et al 2002. Jarrold et al (2000) found no difference in articulation rates of individuals with DS and individuals with moderate learning difficulties, despite significantly poorer digit span performance in the individuals with DS.…”
mentioning
confidence: 99%
“…It was only on some areas where high functioning children performed better than low functioning ones, such as Listening Recall, which is a sub-component of Verbal Working Memory [33][34][35]. The Listening Recall task appears to be quite difficult compared to Digit Recall and Counting Recall tasks within the Verbal Working Memory.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis by Naess, Halaas Lyster, Hulme, and Melby-Lervag (2011) reported significant differences between individuals with DS and typically developing (TD) controls matched on nonverbal mental age in receptive vocabulary, expressive vocabulary and receptive grammar. Working memory, the system that deals with current information, whether newly learned or pulled from long-term memory, is also impaired in DS (Jarrold & Baddeley, 2001;Marcell & Weeks, 1988;McDade & Adler, 1980), beyond even what would be expected for mental age (Kay-Raining Bird & Chapman, 1994;Mackenzie & Hulme, 1987) and IQ (Fidler et al, 2005;Marcell, Harvey & Cothran, 1988;Marcell, Ridgeway, Sewell & Whelan, 1995;Marcell & Weeks, 1988;McDade & Adler, 1980). Naess and colleagues' (2011) meta-analysis also examined verbal short term memory and found deficits for those with DS in comparison to TD participants matched on nonverbal mental age.…”
Section: Down Syndromementioning
confidence: 99%